Analysis of clinical symptoms, radiological changes and pulmonary function data 4 months after COVID‐19. (29th June 2021) - Labarca, Gonzalo; Henríquez‐Beltrán, Mario; Lastra, Jaime; Enos, Daniel; Llerena, Faryd; Cigarroa, Igor; Lamperti, Liliana; Ormazabal, Valeska; Ramirez, Carlos; Espejo, Eric; Canales, Nicole; Fuentes, Fabiola; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) ranges from asymptomatic disease to respiratory failure and requires invasive mechanical ventilation (IMV). Data about the sequelae after infection are scarce. The study aims to describe the prevalence of symptoms, pulmonary function tests (PFTs), and radiological changes after four months of follow‐up. Methods: A prospective, cross‐sectional, multicentre study was performed. Patients with different illness severities were consecutively included (mild; moderate: hospitalized without IMV; severe: hospitalized with IMV). Clinical variables, health‐related quality of life (HRQoL), PFT (spirometry, diffusing capacity of the lungs for carbon monoxide (DLCO)), and (CT) scans of the chest were obtained. The association between the risk of sequelae (DLCO <80%) and altered CT was analysed using logistic regression adjusted for confounding variables. Results: 60 patients (18 mild, 17 moderate, and 25 severe) were included. Fatigue was found in 11% of the mild, 47% of the moderate and 36% of the severe group. Altered DLCO (mild: 5.5%, moderate: 41%, severe: 28%, p  < .05) and change in HRQoL (mild: 50%, moderate: 94%, severe: 60%), while the severe group showed a higher prevalence of altered CT (88% vs. 64%). Awake prone position (APP) and high‐flow nasal cannula (HFNC) was independently associated with altered DLCO, Odds ratio (OR) 7.28 (CI, 1.10‐47.81; p  < .05), and altered CT, OR 9.50 (CI, 1.26‐71.5; p  < .05). Besides, prolonged time in IMV was associated with altered CT, OR 1.24 (CI, 1.05‐1.46; p  < .05). Discussion: It is common to find sequelae in symptoms, radiology, and PFT. In our series, the use of APP+HFNC and days on IMV were associated with an increased risk of sequelae.